The Theories on the Collision of Traditional and Juditial Constitutionalism in the United States of America - Jelena Trajkovska Hristovska (Law Review ,,Iustinianus Primus", 2020)
The phenomenon of judicial supremacy is subjected to criticism of the traditional views on the constitutionalism in the USA. It seems that the clash between the concept of separation of powers on the one hand vs. the role of the courts in interpreting the "invisible constitution" on the other hand still occupies the American scientific community. There is still an impression that it is not ready to propose fundamental changes in the system, so today the judicial supremacy, as a replacement for the judicial review of constitutionality, is considered as the guardian of the Constitution, guardian of the individual rights and guardian of the rights of the minorities. These are basically the values of which no one wants to give up, no matter how much the ambition of the judicial power and its involvement in the political gaps is being criticized. This paper will provide an overview of several theoretical perspectives aimed at conforming judicial review of constitutionality, even through its radical extension in the form of judicial supremacy, judicial activism and judicial paramontcy and the established system of organization of powers.
Keywords: Judicial activism, Judicial constitutionalism, Judicial sef-restrainted, “Living Constitution”, Legal pragmatism, Judicial minimalism, The original intent theory, Theory of original meaning.